The value of “health” in the hierarchy of schoolchildren’s life priorities - Bakiko , Ihor (Sportyvnyi Visnyk Prydniprovia, 2026)
Introduction. Research into the value of “health” in the hierarchy of life priorities of schoolchildren is scientifically and socially significant, as it is aimed at increasing the effectiveness of the educational process, forming a responsible attitude towards one’s own health, and creating the prerequisites for the harmonious development of the individual in modern society. The purpose of the study. The purpose of the study is to investigate what place the value of "health" occupies among the terminal values of schoolchildren in grades 5-11. Methods: analysis of scientific and methodological literature, M. Rokych’s questionnaire of value orientations, methods of mathematical statistics. Results. The most important terminal values for boys are: health (physical and mental) – 31.37 points; good and loyal friends – 31.13 points; pleasure (a life full of pleasures, pleasant pastimes, lots of entertainment) – 30.68 points; love (spiritual and physical closeness with a loved one) – 30.48 points and self-confidence (freedom from internal contradictions, doubts) – 30.28 points. A similar trend is observed for girls. They attributed to the core values: good and loyal friends – 31.03 points; health (physical and mental) – 30.84 points; pleasure (a life full of pleasures, pleasant pastimes, lots of entertainment) – 30.78 points; love (spiritual and physical intimacy with a loved one) – 30.6 points and, unlike boys, interesting work – 30.47 points. Conclusions. Thus, health occupies a leading place in the system of terminal values of schoolchildren, regardless of gender. Its high rating reflects the growing awareness of the importance of physical, mental and social well-being in modern society. The formation of the value of “health” can be considered as an important indicator of the individual’s readiness for a conscious choice of health-preserving behavior and an active life position in the future.